The long-term oral administration of thyroxine: effects on blood hematological and biochemical features in broiler breeder hens. (9th July 2019) - Keshavarz, R; Akhlaghi, A; Zamiri, M J; Jafarzadeh Shirazi, M R; Saemi, F; Akhlaghi, A A; Zhandi, M; Afrouziyeh, M; Zuidhof, M J
Abstract: Published data on the beneficial effect of short-term administration of thyroxine (T4 ) in broiler breeder hens to reduce the ascites incidence in their progeny chicks raises the question as to what extent might the long-term maternal administration of T4 affect the blood hematological and biochemical attributes in breeder hens. A total of 70 broiler breeder hens (47-wk-old) were randomly allotted to control or thyroxine treated (T4 ) groups. Pure T4 (0.3 mg/bird per day) was orally administered to T4 birds for 14 successive weeks, whereas the control group received the drinking water only. Blood samples were obtained from the brachial vein prior to the initiation of the trial as well as weeks 50, 53, 55, 57, 59, and 61 of age. Body weight was decreased but egg production was not affected by T4 treatment. Plasma concentration of T4, but not triiodothyronine (T3 ), was increased in T4 -treated hens ( P < 0.05). The total number of leukocytes and erythrocytes were also higher in T4 birds. A significant effect of time was observed for erythrocyte number and plasma cholesterol concentration ( P < 0.05). The long-term administration of T4 did not affect the concentrations of serum calcium and plasma total protein, albumin, globulin, cholesterol, triglyceride, high density lipoprotein, low density lipoprotein, very low density lipoprotein, alanine amino transferase, and aspartate amino transferase ( P > 0.05). However, serum concentrations of phosphorus, glucose, and alkaline phosphatase were higher in T4 hens as compared to their control counterparts. In spite of differences in circulatory concentrations of a number of traits between the experimental groups, the recorded values were within their reference ranges. Therefore, the administration of T4 for an extended period of time had no apparent adverse effect on the clinical profile in subjected hens, which may practically support the implementation of this preventative treatment as an approach to decrease the ascites incidence; however, a lower incidence rate in the progeny chicks produced from hens receiving T4 for long-term periods of time remains to be elucidated.